The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-83887-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals KRTAP1-1 as a novel genetic variant associated with antidepressant treatment outcomes

Abstract: Achieving remission following initial antidepressant therapy in patients with major depressive disorder (MDD) is an important clinical result. Making predictions based on genetic markers holds promise for improving the remission rate. However, genetic variants found in previous genetic studies do not provide robust evidence to aid pharmacogenetic decision-making in clinical settings. Thus, the objective of this study was to perform whole-genome sequencing (WGS) using genomic DNA to identify genetic variants as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Pro les of germline variants and MDD-related genes After the systematic literature review, a total of 44 MDD-related genes were identi ed, and 40 of the 44 genes were found in the current study in 367 patients with MDD (Supplementary Table S1) [4,5,13,[35][36][37][38][39][40][41][42][43]. Rare exonic missense variants (with MAF less than 1%) of these genes were selected using the 1000 Genomes Project data, the Korean Variant Archive [44], and the Genome Aggregation Database.…”
Section: Resultsmentioning
confidence: 99%
“…Pro les of germline variants and MDD-related genes After the systematic literature review, a total of 44 MDD-related genes were identi ed, and 40 of the 44 genes were found in the current study in 367 patients with MDD (Supplementary Table S1) [4,5,13,[35][36][37][38][39][40][41][42][43]. Rare exonic missense variants (with MAF less than 1%) of these genes were selected using the 1000 Genomes Project data, the Korean Variant Archive [44], and the Genome Aggregation Database.…”
Section: Resultsmentioning
confidence: 99%
“…The current consensus of how MDD develops in an individual and the causes of the disorder are a culmination of genetic, psychological, and environmental factors ( Bromet et al, 2011 ). MDD acts on the brain and most notably affects the process of neurotransmitters and synaptic activity in the forebrain region ( Park et al, 2021 ). Neurotransmitters, like serotonin, norepinephrine, and dopamine, are essential for regulating the central nervous system (CNS) ( Goldstein et al, 2015 ).…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%
“…A significant portion of those diagnosed with MDD are thought to be genetically predisposed to the disorder, as MDD is known to affect entire families in some cases ( Klein et al, 2001 ). Genetic studies have shown that MDD has a significant overlap with genes associated with other psychiatric disorders ( Park et al, 2021 ). The genetics of major depressive disorder reveal polygenic risk scores on an individual basis, but there is no official manner of treatment or diagnosis provided through one’s genetics ( Fabbri et al, 2020 ).…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%
“…Whole genome sequencing (WGS) can provide information regarding all genetic variants-rare variants, loss of function (LOF), functional intronic variants, and structural variants. Significant outcomes from studies on these variants can provide useful information to pinpoint causal genes and their associated pathways (Park et al, 2021). Hence, this study aims to explore whole genome sequencing in male and female Wistar rats susceptible to depression.…”
Section: Introductionmentioning
confidence: 99%